The revised OECD Guidelines: A strengthened forum for resolving ESG disputes? - Laurie Achtouk-Spivak; Robert Garden (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
The 2023 OECD Guidelines for Multinational Enterprises on Responsible Business Conduct contain various revisions to their self-contained dispute resolution mechanism, before National Contact Points established by adhering States. This Perspective explores the revisions and the potential of the revised mechanism to "bite" multinational enterprises.
Keywords: 330